Pelatihan Pengenalan Koding dan Kecerdasan Artifisial Pada Guru Sekolah Dasar - Nursalam; Rufaida, Salwa; Aeni Rahman, Syarifah; Khatimah, Husnul; Nur Intan, Sry; Risani, Arni (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The development of digital technology requires educators to master 21st-century skills, including digital literacy and computational thinking. Although the government encourages the integration of coding and artificial intelligence in the curriculum, there is still a significant competency gap among elementary school teachers, especially at Cambaya IV Elementary School in Makassar, where most teachers do not yet understand the basic concepts or application of these technologies in learning. This community service activity aims to provide practical training in coding and artificial intelligence in order to improve conceptual understanding and digital skills, as well as motivate teachers to create an innovative learning environment for students. The implementation method consisted of three main stages, namely planning through material preparation and technical coordination, implementation consisting of introductory sessions on coding and artificial intelligence, training with a hands-on approach both without devices and using applications, and mentoring to help teachers apply the material independently. The final stage was reporting, which involved reflection and evaluation of the entire series of activities. The results of the activity showed a significant increase in the understanding, confidence, and motivation of all participating teachers in integrating coding and artificial intelligence into learning. Through hands-on practice using device-free methods and application-based methods such as ScratchJr and simple artificial intelligence platforms, teachers gained concrete experiences that were useful for developing creative teaching strategies. The conclusion of this activity is that hands-on training and contextual mentoring have proven effective in improving teachers' technological competencies through the active involvement of the educational community. An important new aspect of this activity confirms that strengthening teachers' capacity through practical experience is key to supporting the transformation of digital literacy at the elementary school level.